Study of the Formation and Thermal Stability of mg2co Obtained by Mechanical Alloying and Heat Treatment - Ordonez, S; Serafini, D (2014)
The microstructural evolution of Mg and Co in a 2:1 atomic ratio was investigated during mechanical alloying and subsequent heat treatments. Microstructural characterization was determined using X-ray diffraction and scanning electron microscopy, while thermal stability was studied by means of differential scanning calorimetry. The results show that mechanical alloying produces amorphization and promotes greater microstructural refinement. Formation of Mg2Co requires an additional heat treatment at temperatures between 679 and 705 K, depending on milling time. Additionally, it was determined that the activation energy for Mg2Co crystallization decreases from 206 to 184 kJ/mol when the milling time increases from 12 to 36 h, respectively. Finally, a combination of the mechanical alloying process and heat treatment phase evolutions was proposed as an optimal processing route in order to obtain the Mg2Co compound. © 2013 Elsevier B.V. All rights reserved.